EFEKTIVITAS PROGRAM CERITA KOLONG LANGIT DALAM PEMBELAJARAN LITERASI DASAR UNTUK PENGENTASAN BUTA HURUF PARSIAL DI SATU AMAL INDONESIA KOTA PALEMBANG - Nurfadya Pane, Aisyah; Hartono, Yusuf; Husin, Azizah; Aswasulasikin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the effectiveness of the Cerita Kolong Langit Program in improving basic literacy skills to reduce partial illiteracy among participants at Satu Amal Indonesia in Palembang. Using a quantitative approach and a quasi-experimental one-group pretest posttest design, the research involved 40 children aged 7 - 12 years at Taman Bacaan Sungai Ijuk. Data were collected through pre-test, post-test, structured observation, and documentation, then analyzed with descriptive statistics, the Shapiro–Wilk test, paired sample t-test, and normalized gain. The results show a significant increase in literacy achievement with a significance value of 0.000 < 0.05. The mean score rose from 58.40 to 86.28, while the overall N-gain reached 0.670 in the medium category. The lower class obtained an N-gain of 0.638 and the upper class reached 0.702. Program implementation was supported by a warm learning climate, patient and adaptive tutors, contextual stories, and creative activities. The main constraints were irregular attendance, unequal initial ability, limited instructional time, and uneven literacy practice at home. These findings indicate that the program is effective and feasible to be developed further as a community based basic literacy model.